Study of Wintering Strategy of Common Coot Fulica atra in Guerbes-Sanhadja Wetlands (Skikda, North-Eastern Algeria) - Aouissi, A; Sedddik, S; Boudraa, W; Houhamdi, M. (My University, 2018)
The monitoring of common coot Fulica atra (Rallidae) ecology was done in Guerbes-Sanhadja wetlands. The results showed that this bird was abundant in these sites. In this study, it could be noted that at the level of these aquatic ecosystems, Common Coot due to its gregarious character have been concentrated in water far from the banks of the sites studied near the tufts of Typha angustifolia and Scirpus lacustris, and formed two distinct groups. The study of the diurnal activity rhythms throughout the wintering period has shown that feeding has dominated by far the total balance sheets, and this in all the wetlands which showed the role of daytime gaining ground of these bodies of water. This was observed in the water (by spout, immersion of the head in the water, by tilting of the front of the body in the water) and on the banks (grazing grass near the belts of water